From Glucose to Lactate and Transiting Intermediates Through Mitochondria, Bypassing Pyruvate Kinase: Considerations for Cells Exhibiting Dimeric PKM2 or Otherwise Inhibited Kinase Activity - Chinopoulos, Christos (Frontiers in Physiology, 2020)
A metabolic hallmark of many cancers is the increase in glucose consumption coupled to excessive lactate production. Mindful that L-lactate originates only from pyruvate, the question arises how can this be sustained in those tissues where pyruvate kinase activity is reduced due to dimerization of PKM2 isoform or inhibited by oxidative/nitrosative stress, posttranslational modifications or mutations, all widely reported findings in the very same cells. Hereby 17 pathways connecting glucose to lactate bypassing pyruvate kinase are reviewed, some of which transit through the mitochondrial matrix. An additional 69 converging pathways leading to pyruvate and lactate but not commencing from glucose are also examined. The minor production of pyruvate and lactate by glutaminolysis is scrutinized separately. The present review aims to highlight the ways through which L-lactate can still be produced from pyruvate using carbon atoms originating from glucose or other substrates in cells with kinetically impaired pyruvate kinase, and underscore the importance of mitochondria in cancer metabolism irrespective of oxidative phosphorylation.